2019
DOI: 10.1001/jama.2019.10551
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intensive vs Standard Blood Pressure Control With Cerebral White Matter Lesions

Abstract: The effect of intensive blood pressure lowering on brain health remains uncertain. OBJECTIVE To evaluate the association of intensive blood pressure treatment with cerebral white matter lesion and brain volumes. DESIGN, SETTING, AND PARTICIPANTS A substudy of a multicenter randomized clinical trial of hypertensive adults 50 years or older without a history of diabetes or stroke at 27 sites in the United States. Randomization began on November 8, 2010. The overall trial was stopped early because of benefit for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
228
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 324 publications
(259 citation statements)
references
References 39 publications
12
228
3
2
Order By: Relevance
“…In terms of the cardiovascular risk factors, hypertension is a major driver of SVD (41), and ambulatory measurements of blood pressure are better predictors of WMH than self-reported measurements (42). In the setting of hypertension, the risk of accumulating WMH rises rapidly above a resting systolic blood pressure of approximately 120 mmHg (43). Systolic blood pressure sustained above this threshold also predicts a growing risk for dementia and strokes (42, 44).…”
Section: Who Is a Candidate For Svd?mentioning
confidence: 99%
“…In terms of the cardiovascular risk factors, hypertension is a major driver of SVD (41), and ambulatory measurements of blood pressure are better predictors of WMH than self-reported measurements (42). In the setting of hypertension, the risk of accumulating WMH rises rapidly above a resting systolic blood pressure of approximately 120 mmHg (43). Systolic blood pressure sustained above this threshold also predicts a growing risk for dementia and strokes (42, 44).…”
Section: Who Is a Candidate For Svd?mentioning
confidence: 99%
“…However, this study displayed a trend towards a reduction in mild cognitive impairment. The recent SPRINT MIND substudy found a smaller increase in white matter lesions in the intensive group but a greater decrease in total brain volume in this group, although with small differences [157]. In the past few years, several studies have raised concerns about the possible negative impact of excessive BP reduction in elderly patients (>80 years old) [158].…”
Section: For the Future?mentioning
confidence: 99%
“…Today, there is a strong evidence that hypertension in the elderly as well as in the very elderly must be treated and this is supported by international guidelines and a Cochrane meta-analysis (9-13). A sub-analysis of the Systolic Blood Pressure Intervention Trial (SPRINT) in elderly has recently confirmed the benefits of lowering BP in hypertensive patients older than 75 years with some potential benefits on cognitive function and white matter lesions (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 97%